Spectrin-based pathways underlying electrical and mechanical dysfunction in cardiac disease - Hund, Thomas J. (Expert Rev Cardiovasc Ther, 2017)
INTRODUCTION: In the heart, pathways that transduce extracellular environmental cues (e.g. mechanical force, inflammatory stress) into electrical and/or chemical signals at the cellular level are critical for the organ-level response to chronic biomechanical/neurohumoral stress. Specifically, a diverse array of membrane-bound receptors and stretch-activated proteins converge on a network of intracellular signaling cascades that control gene expression, protein translation, degradation and/or regulation. These cellular reprogramming events ultimately lead to changes in cell excitability, growth, proliferation, and/or survival. AREAS COVERED: The actin/spectrin cytoskeleton has emerged as having important roles in not only providing structural support for organelle function but also in serving as a signaling “super highway,” linking signaling events at/near the membrane to distal cellular domains (e.g. nucleus, mitochondria). Furthermore, recent work suggests that the integrity of the actin/spectrin cytoskeleton is critical for canonical signaling of pathways involved in cellular response to stress. This review discusses these emerging roles for spectrin and consider implications for heart function and disease. EXPERT COMMENTARY: Despite growth in our understanding of the broader roles for spectrins in cardiac myocytes and other metazoan cells, there remain important unanswered questions, the answers to which may point the way to new therapies for human cardiac disease patients.